Dynamics of blood glucose concentration after a food determines subsequent energy consumption: Dynamics of blood glucose concentration - Zafar, Tasleem A; Allafi, Ahmad R (Progress in Nutrition, 2019)
Obesity and its related comorbidities such as type 2 diabetes and cardiovascular disorders are global public health challenges. It is imperative to understand patterns of the dietary composition that regulate blood glucose concentration, satiety cues, and energy consumption. Objectives: This study elucidated the dynamics of blood glucose concentration after a test food as a crucial determinant of appetite and energy intake at a subsequent meal. Methods: Both low and high glycemic index (GI) foods in liquid and solid forms or fixed available carbohydrate and in equicaloric amounts were tested in healthy female volunteers (n=14/experiment) on blood-glucose and percent energy compensation (%EC). White wheat bread (solid, high-GI) was compared with chickpeas (solid, low-GI) at 50 g available-carbohydrate in Experiment 1 and Coca-Cola (liquid, high-GI) with skim milk (liquid, low-GI) and chickpeas (solid, low-GI) at equicaloric amounts in Experiment 2. Blood glucose and appetite were measured at baseline and over time up to two hours in Experiment 1 and one hour in Experiment 2. Caloric intake was estimated from a pizza-meal at the end of the studies and %EC calculated. Results: Both high GI foods had the largest glucose peaks; chickpeas had an intermediate and milk the smallest peak. Blood glucose concentration before meal time was associated with energy intake. The %EC was: chickpeas (70%) > bread (7%) in Experiment 1; and chickpeas (80%) > milk (40%) > Coca-Cola (32%) in Experiment 2. Conclusions: Intake of foods with low GI value would prove helpful in the prevention and controlling of obesity, hyperglycemia or hyperinsulinemia.